Non-ammonoid cephalopods of the Early Permian Shakhtau reef (Republic of Bashkortostan, Russia) - A.Yu. Shchedukhin (Учёные записки Казанского университета: Серия Естественные науки)
This article presents the results of a study of new cephalopod collections from the Shakhtau quarry. The latter has so far been little explored as a separate locality of cephalopods: the first descriptions of several pseudorthoceratid species from the Shakhtau reef massif were made in the mid-20th century, only from the Artinskian part of it, and contained the lists of the numerous Asselian-Sakmarian nautilids, without descriptions; a more detailed study of the Shakhtau cephalopod complexes has been carried out relatively recently. In this study, two representatives of the order Pseudorthoceratida were recorded for the first time in the Asselian-Sakmarian deposits of the Shakhtau locality: Uralorthoceras tzwetaevae Shimansky and Kionoceras serenum Shimansky. Additionally, several forms of the order Nautilida were newly identified here: Gzheloceras uralense Ruzhencev et Shimansky, ?Temnocheilus sp. A; two new genera (Genus A and Genus B) from the family Rhiphaeoceratidae and two new forms related to the family Grypoceratidae (Genus C and Genus D), with an intricately dissected suture line. They may belong to a new family of the Permian nautilids. In the Asselian-Sakmarian community, they are both related to the Carboniferous and completely new species and genera of nautilids. The ratio of life forms brings the near-riff Asselian-Sakmarian community of the Shakhtau quarry closer to the similar Kazanian (Roadian) community from the Volga-Ural region. The results obtained are of great importance for understanding and reconstructing the evolutionary pathways of the Early Permian non-ammonoid cephalopods.